Sperm histone H3 lysine 4 trimethylation is altered in a genetic mouse model of transgenerational epigenetic inheritance. Issue 20 (17th October 2020) - Lismer, Ariane; Siklenka, Keith; Lafleur, Christine; Dumeaux, Vanessa; Kimmins, Sarah
Abstract: Advancing the molecular knowledge surrounding fertility and inheritance has become critical given the halving of sperm counts in the last 40 years, and the rise in complex disease which cannot be explained by genetics alone. The connection between both these trends may lie in alterations to the sperm epigenome and occur through environmental exposures. Changes to the sperm epigenome are also associated with health risks across generations such as metabolic disorders and cancer. Thus, it is imperative to identify the epigenetic modifications that escape reprogramming during spermatogenesis and embryogenesis. Here, we aimed to identify the chromatin signature(s) involved in transgenerational phenotypes in our genetic mouse model of epigenetic inheritance that overexpresses the histone demethylase KDM1A in their germ cells. We used sperm-specific chromatin immunoprecipitation followed by in depth sequencing (ChIP-seq), and computational analysis to identify whether differential enrichment of histone H3 lysine 4 trimethylation (H3K4me3), and histone H3 lysine 27 trimethylation (H3K27me3) serve as mechanisms for transgenerational epigenetic inheritance through the paternal germline. Our analysis on the sperm of KDM1A transgenic males revealed specific changes in H3K4me3 enrichment that predominantly occurred independently from bivalent H3K4me3/H3K27me3 regions. Many regions with altered H3K4me3 enrichment in sperm were identified on the paternal allele of the pre-implantation embryo. These findings suggest that sperm H3K4me3 functions in the transmission of non-genetic phenotypes transgenerationally.